Chemical emergencies management : The Department of Environment perspective - Pachaimuthu, Vellayutham (2021)
In the event that incidents such as fires, explosions or leakages involving chemicals occur in major hazardous installations, The Occupational Safety and Health (Control of Industrial Major Accident Hazards) (CIMAH) Regulations 1996, would operate to control the onsite situation. However, should such incidents escalate into disasters, there is the National Security Council's Directive 20 that outlines a policy to manage them. As a supporting agency under this Directive 20, the Department of Environment (DOE) is entrusted to fulfill its primary function of preventing and controlling pollution. The objective of this study is to evaluate that state of preparedness, both at the headquarters as well as the state level, as regards to the availability of equipment, the personnel's competence to handle monitoring, communication and safety equipment, their knowledge of the roles and responsibilities of DOE as a responding agency and about the contents of Directive 20. Information gathered was by way of a questionnaire targeted at different levels of the DOE personnel and it covered the various areas of focus outlined in the objective. The measurements of the variables were then quantified by devising a rating scale and analysed statistically using the SPSS program. The t- Test method of comparison of the means was also utilised to compare the headquarters and state groups. A Checklist and Audit of the availability and condition of the monitoring, communication and safety equipment needed during a chemical emergency were also carried out. Then, an Emergency Response Plan was formulated in line with DOE's role under Directive 20. The findings of the study indicate that though the personnel's knowledge of the roles and responsibilities of DOE is good, their understanding of Directive 20 is insufficient, and their ability to handle monitoring, communication and safety equipment is lacking. Capacity building programs such as trainings for the personnel and exercises to test its preparedness would be able to enhance DOE's capability and overcome any shortcoming in the management of a chemical emergency.